"I received a leaflet and that is all": Father experiences of a diagnosis of autism. (28th December 2016) - Potter, Carol A.
Abstract : Accessible summary: Little is known about what fathers think and feel about a diagnosis of autism. Fathers experienced strong emotion around diagnosis and were given little support. Services should support mother and fathers in ways which meet their individual needs. More positive messages should be given to families at diagnosis. Abstract: Background: A diagnosis of childhood autism can be an extremely stressful experience for parents, but little is known concerning paternal perceptions of the process. Methods: This study investigated father perspectives on a diagnosis of autism, through an online survey. Results: An analysis of 184 replies to an open‐ended question identified the following themes: strong initial emotional response and a range of immediate anxieties about the future, struggle to gain a diagnosis; anger in response to insensitive delivery of diagnosis together with insufficient information at the time and lack of support afterwards. Conclusion: Fathers experienced a range of significant challenges during a diagnostic process in which most felt unsupported. Service provision should be more gender‐differentiated, taking into account of the particular needs and perspectives of both mothers and fathers at this critical juncture in family life.